Corporalidad del migrante y desplazamiento urbano: la ciudad desde el exceso corporal en dos novelas del Cono Sur - Paula González León (Nuevo mundo - Mundos Nuevos, 2019)
The aim of this work is to reflect on the materialities behind the contacts established between the subjects, others and cities. This in order to defend the thesis that within the relational framework that is woven between the city and the migrant subjects, the protagonists of the novels remain prisoners of a constant wandering that makes their permanent inscription difficult, which would bring with it difficulties at the level of their subjectivation. This would then make the subjects install themselves from a position that supposes the tension between two spaces, which makes their affirmation in the terrain of the city difficult but, at the same time, they cannot abandon it completely either.